On demande toujours des inventeurs et l'on cherche encore les innovateurs - Jean-François Cerisier (Centre National d'Enseignement à Distance, 2015)
For various reasons, and for decades, the topic of innovation in education has been flaunted as a slogan by many political leaders but also by many educators. The use of digital media in education is at the heart of this question. Several issues are often intermingled: some related to the invention of new practices and the role played by technology, others related to socialization of these inventions and some others relating to their real value. Geneviève Jacquinot-Delaunay very early undertook numerous researches that contributed to clarify this question. She tries in particular to show how and why the specificity of the media is almost never taken into account. She also undertakes to develop new propositions to understand better the innovation processes and how we can manage them. This article discusses the concepts of invention and innovation in the wake of the work of Geneviève Jacquinot-Delaunay and of the scientific community she greatly contributed to develop and animate in an interdisciplinary perspective. It deals with the model of the digital instrumentation of activity and its two subsequent dimensions - instrumental mediation and instrumental genesis for understanding the invention and innovation processes. Finally, it proposes a new model about the proximal zone of instrumental development and briefly confronts the model with the reality of the current policy of massive deployment of tablet PCs in school education.